(untitled) (Journal of Hama University, 2020)
Irrigation is often considered the most important part of endodontic treatment, particularly when it comes to its anti-bacterial effect. During the preparation of the canals using the endodontic instruments, irrigation solutions kill microbes and preparation debris. Aim of the Study : This study aims to evaluate and compare the depth of the penetration of sodium hypochlorite inside the dentinal tubules using different methods of irrigation and activation to determine the best available method to get to the highest possible penetration inside the dentinal tubules Materials and Methods : The study samples 60 newly extracted single-root and single-canal teeth. The samples were normalized at 16mm starting from the apex and randomly distributed into 5 groups, Where the irrigation was done in the first group with sodium hypochlorite using irrigation needles, whereas in the second group irrigation was done with sodium hypochlorite after using EDTA, while in the third, fourth and fifth groups, irrigation with sodium hypochlorite was activated and activated using ultrasound and sound waves and the ER: YAG laser, respectively.The canals were prepared with the Mtwo system until #35 along the entire working length and the apices were closed using wax. The teeth were then submerged for 48 hours in violet crystal pigment at 37 degrees (C). The teeth were then washed with running water to flush away the pigment. The different irrigation methods were applied to each corresponding group then examined under a stereoscope after performing longitudinalsections. The depth of penetration was measured using the MicroDicom software. The results show that the highest depth of penetration was associated with using the ultrasonic activation method when compared to the other groups. The results also show that the sonic activation method outperforms the ER:YAG laser activation. EDTA was associated with more penetration inside the dentinal tubules.